Role of TSLP signaling in airway structural cells during rhinovirus infection in regard to asthma - Harbo,Ebba (2023)
Asthma is a chronic inflammatory condition caused by a complex interaction between genetic and environmental factors. The immune response to various environmental triggers is thought to play a major role in driving the chronic inflammation in asthma. The most common trigger related to asthma exacerbations are infections with rhinovirus (RV). RV triggered bronchial epithelial cells (BECs) have shown to secrete the alarmin thymic stromal lymphopoietin (TSLP), a potent upstream mediator inducing type 2 immunity. Interestingly, the novel biologic tezepelumab, an anti-TSLP monoclonal antibody, has been demonstrated to reduce asthma exacerbations in patients with uncontrolled asthma. Additionally, clinical tezepelumab treatment have reduced the production of IL-33 in BECs after viral stimuli. However, there is little knowledge regarding paracrine and autocrine TSLP signaling of the bronchial epithelium. Thus, I aimed to study the molecular and functional role of TSLP stimulation on the bronchial epithelium and in the crosstalk between bronchial epithelium and bronchial smooth muscle cells (BSMC). In this report we showed that TSLP reduced the anti-viral resistance in BECs as IFN-beta was significantly reduced after viral infection in TSLP primed BECs. TSLP also decreased anti-viral tolerance as IL-8 and TNFalfa was increased after RV infection in TSLP primed BECs. Further, we showed that the immunoregulatory role of TSLP is mostly associated to its influence on the bronchial epithelium, as TSLP itself did not trigger direct immune responses in BSMCs. Instead, we found that supernatants from TSLP primed BECs stimulated immune responses in BSMCs, indicating other mediators to be the effector molecules in the crosstalk between BECS and BSMCs. Further investigations on the role of TSLP in asthma need to be performed to fully understand its underlying mechanisms and how it is used to treat asthma exacerbations.